Synthesis of Lactulose in Continuous Stirred Tank Reactor With β-Galactosidase of Apergillus oryzae Immobilized in Monofunctional Glyoxyl Agarose Support - Ubilla, Claudia; Ramírez, Nicolás; Valdivia, Felipe; Vera, Carlos; Illanes, Andrés; Guerrero, Cecilia (Frontiers in Bioengineering and Biotechnology, 2020)
Lactulose synthesis from fructose and lactose in continuous stirred tank (CSTR) reactor operation with glyoxyl-agarose immobilized Aspergillus oryzae β-galactosidase is reported for the first time. The effect of operational variables: inlet concentrations of sugar substrates, temperature, substrate molar ratio, enzyme loading and feed flow rate were studied on reactor performance. Even though the variation of each one affected to a certain extent lactulose yield (YLactulose), specific productivity (πLactulose) and selectivity of the reaction (lactulose/TOS molar ratio) (SLu/TOS), the most significant effects were obtained by varying the inlet concentrations of sugar substrates and the feed substrate molar ratio. Maximum YLactulose of 0.54 g·g -1 was obtained at 50 °C, pH 4.5, 50 % w/w inlet concentrations of sugar substrates, feed flowrate of 12 mL·min-1, fructose/lactose molar ratio of 8 and reactor enzyme load of 29.06 IUH·mL-1. At such conditions YTOS was 0.22 g·g -1, SLu/TOS was 3.7, lactose conversion (XLactose) was 0.39. and total transgalactosylation yield was 0.762 g·g -1, meaning that 76 % of the reacted lactose corresponded to transgalactosylation and 24 % to hydrolysis, which is a definite advantage of this mode of operation. Even though XLactose in CSTR was lower than in other reported modes of operation for lactulose synthesis, transgalactosylation was more favored over hydrolysis which reduced the inhibitory effect of galactose on β-G.